2017
DOI: 10.1002/lt.24696
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life after pediatric liver transplantation: A systematic review

Abstract: With improved survival rates after pediatric liver transplantation (LT), attention is targeting improving the health-related quality of life (HRQOL) as an outcome metric. We conducted a systematic review of the literature to examine HRQOL after pediatric LT, focusing on assessment tools and factors associated with HRQOL. A literature search was conducted through PubMed, Web of Science, Ovid, and Google Scholar for all studies matching the eligibility criteria between January 2004 and September 2016. Titles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 46 publications
5
74
1
2
Order By: Relevance
“…Further delay will only result in children being at risk of irreversible damage for longer. There are also psychological and quality‐of‐life benefits to early transplantation . Thus, where transplantation is indicated, it should not be delayed and, ideally, should be scheduled in the preschool period.…”
Section: Discussionmentioning
confidence: 99%
“…Further delay will only result in children being at risk of irreversible damage for longer. There are also psychological and quality‐of‐life benefits to early transplantation . Thus, where transplantation is indicated, it should not be delayed and, ideally, should be scheduled in the preschool period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HRQoL in pediatric LT recipients most frequently assess self- and parent-reported HRQoL determinations via the utilization of validated age-appropriate instruments and have explored the associations between demographic or medical variables and HRQoL outcomes [3, 4]. Two systematic reviews evaluating HRQoL outcomes in pediatric LT recipients underscore HRQoL being lower than healthy controls, although comparable to children with chronic diseases or other pediatric solid organ transplant recipients [5, 6]. The more recent systematic review by Parmar et al [5] highlighted the contribution to the field of newer disease-specific tools, although interventional studies targeting strategies to address this decreased HRQoL remain sparse [5].…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews evaluating HRQoL outcomes in pediatric LT recipients underscore HRQoL being lower than healthy controls, although comparable to children with chronic diseases or other pediatric solid organ transplant recipients [5, 6]. The more recent systematic review by Parmar et al [5] highlighted the contribution to the field of newer disease-specific tools, although interventional studies targeting strategies to address this decreased HRQoL remain sparse [5]. Additional ways to better understand the challenges experienced by this patient population are needed to enhance our ability to derive novel strategies.…”
Section: Introductionmentioning
confidence: 99%
“…24 With more patients surviving longer, however, there has also been an increase in the long-term complications of transplantation. 5 In addition to other organ toxicities, allograft loss, and impaired health-related quality of life, 6, 7 a dramatic increase in cancer incidence has been seen in organ transplant recipients. 8, 9 The overall increased incidence of malignancy in patients who have received solid organ transplants has been reported to range from a two- to six-fold increase above the general population, 8, 10 depending on the cohort and type of transplant.…”
mentioning
confidence: 99%
“…19, 24 Given the huge economic burden of these oncologic diagnoses on the health care system 25 and quality of life for the transplant recipients and families, 6, 26 the observations of Yanik et al encourage further studies to develop improved strategies for preventing these potentially devastating outcomes.…”
mentioning
confidence: 99%